Integrated royalties model to promote the exploration and exploitation of tight reservoirs in North West of Peru - Sinchitullo J. (2019)
Special thanks to the "Master’s Program in Peruvian Universities", promoted by the Ministry of Education (MINEDU), the National Council of Science, Technology and Technological Innovation (CONCYTEC), National Fund for Scientific, Technological and Technological Innovation Development (FONDECYT), Vice-Rectorate for Research of the Universidad Nacional de Ingenieria and CAREC, institutions that made possible the realization of this research article.